Enhancement of the Portfolio Determination using Multi- Objective Optimization - UmaDevi, B; Sundar, D; Alli, P (International Journal of Computer Sciences and Engineering, 2014)
Portfolio construction is enabled through the multi objective optimization. The nature of the problem invites the construction through multi objective optimization. Genetic algorithm and the particle swarm optimization is used for the above purpose. The results obtained are compared against the classical Markowitz model. The data from the Nifty from March 2010 to October 2010 has been used. The Stocks from various sectors are used to build the portfolio. The proposed work is promising and the results obtained are outperforming. Comparing on both the algorithms PSO based multi objective optimization serves better than Genetic algorithms based on the results obtained.